Perancangan Desain Ui/Ux Aplikasi Pelaporan Harian Digital Pada PT. Jasa Marga Tollroad Operator Menggunakan Metode Design Thinking - Aldino Nur Asa Fisabililah; Umi Chotijah (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2023)
User Interface (UI) and User Experience (UX) have an important role in an application design process, because in an application design must be organized and organized, not only that the design of an application must be in accordance with the needs (demands) of potential users. PT. Jasa Marga Tollroad Operator (JMTO) is an Indonesian state-owned enterprise engaged in toll road business. Jasa Marga is the first and largest toll road developer and operator in Indonesia with a market share of 50% for the length of commercial toll roads that have been operating (±1,260 km). With more than 44 years of experience, Jasa Marga currently manages 35 toll road concessions with a total road length of 1,906 km. In the Traffic and Transaction Division of PT. Jasa Marga still uses paper media to record daily activities, both daily reports of officers and minutes of incidents, in doing so officers have problems such as missing report paper, damaged report paper and obstacles in the process of inputting data that is still slow and seems inefficient. Therefore, the Traffic Division of the Krian Gresik Toll Section (KLB) on the occasion of JMIC 2022 has an innovation to create an Android-based Daily Reporting and Event News application to replace paper media. This research aims to implement a method, namely the Design Thinking method which will be used in designing the Android-based JMTO Access v1.0 Digital Reporting application. In designing this application, it was decided to use the Design Thinking method which includes 5 stages, namely emphatize, define, ideate, prototype and test